PENGARUH MODEL PEMBELAJARAN KOOPERATIF STUDENT FACILITATOR AND EXPLAINING (SFAE)TERHADAP PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS XI MIPA SMAN 1 INUMAN - Andri Alpindo (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research represent research of experiment with type of quasi design experimental with research form owning group control etapi [do] not function fully to control external variables which influence execution of experiment. Target of this research to influence Model Study Of Co-Operative of Student Facilitator Explaining and ( SFAE) To Achievement Learn Student [At] Fundamental Discussion Hydrocarbon [in] Class of XI MIPA SMAN 1 Inuman. this research [of] background by lowering of achievement learn educative [by] participant [at] study of chemistry, this matter [is] caused by some of educative [by] participant less participating in study and unable to lay open idea or [his/its] opinion at the (time) of study process. As for sampel of this research that is class of XI MIPA, where class control [is] class of XI MIPA 1 while experiment class [is] class of XI MIPA 2. Pursuant to result of research obtained [by] that there is difference which [is] signifikan [among/between] achievement mean learn student [at] hydrocarbon items [among/between] class applying model study of Student Facilitator Explaining and and class control with value of sig ( 2-tailed) equal to its 0,049 meaning. 0,0049 < 0,05. As for value mean evaluate experiment class that is equal to 86,37 while value mean evaluate class control that is equal to 81,65.